Presence of a Novel Anatomical Structure May Cause Bleeding When Using the Calyx Access in Mini-Percutaneous Nephrolithotomy - Lin, Fangyou; Li, Bojun; Rao, Ting; Ruan, Yuan; Yu, Weimin; Cheng, Fan; Larré, Stéphane (Frontiers in Surgery, 2022)
Background: Fused renal pyramid (FRP) is a kidney anatomical structure which was first identified by us. The vascular anatomy of FRP exhibits different from that of the normal renal pyramid (NRP), manifested by the distribution of the ectopic interlobar arteries in FRP. In this study, we analyzed the effect of FRPs on bleeding when using calyx access in mini-percutaneous nephrolithotomy (PCNL). Patients and methods: Overall, 633 patients who underwent ultrasound-guided single-tract mini-PCNL were divided into two groups according to the puncture method used: in group A, puncture was performed through the axial direction of the renal calyx, the line from the apex of the fornix to the center of the neck plane under B-mode ultrasound guidance; and in group B, Doppler ultrasound-guided axillary puncture through calyces corresponding to NRPs when the plane of renal column blood vessels on both sides was selected or calyx puncture through the hypovascular area of the FRPs. Relevant demographic and clinical data were retrospectively analyzed. Results: The two groups exhibited similar baseline characteristics. No significant differences were found in hemoglobin reduction, puncture site, tract size, postoperative creatinine level, or stone-free rate between the two groups (P>0.05). Blood transfusion and embolization rates in group B were significantly lower than those in group A (P=0.03 and 0.045, respectively). No differences were found between the two groups in terms of persistent pain, hydrothorax, fever, subcapsular hematoma, and urosepsis (P>0.05). The overall complication rate was not significantly different between the two groups (P=0.505). Conclusions: FRP is a non-negligible anatomical structure that may cause hemorrhage when using calyx access. Doppler ultrasound can identify ectopic blood vessels in FRPs to reduce bleeding during calyx access in mini-PCNL procedures.